Toxic effects of 2-dodecanone in the insect model species Chironomus riparius: potential alternatives of secondary metabolites to synthetic insecticides - Pla, C.; Herrero, Ó.; Llorente, L.; Blanco, L.; de la Peña, E.; Planelló, R. (Spanish Journal of Environmental Mutagenesis and Genomics, 2018)
Among the mechanisms of most of plants to defend against insects, glandular trichomes are shoot epidermal hairs responsible for a significant portion of a plant’s secondary metabolites. Some of these substances are weak toxins since they compromise insect survival, and may delay their growth and pupation, making insects more vulnerable. Methyl ketones are a widely-produced group of chemicals synthesized by trichomes and their insecticidal efficacy has been described against some arthropods, such as aphids or spider mites. However, information about the mode of action and molecular effects of these compounds on insects are still very scarce. In the present study, the toxicity of 2-dodecanone (CAS 6175-49-1) was investigated in Chironomus riparius aquatic larvae –an insect model species in ecotoxicology studies–. The effects of acute 24-h and 96-h exposures to a range of doses (0.05 μg/L, 5 μg/L and 500 μg/L) were analysed at the molecular level by analysing changes in the transcriptional activity of genes related to the cell response to stress (hsp70, hsp40, hsp10), detoxification pathways (cyp4G, GST and GPx), endocrine system (EcR and vtg) and DNA repair and apoptosis (XRCC1, NLK, ATM, CASP3). Ribosomal gene 26S, actin and ribosomal protein L13 were used as reference genes. Our results showed that 2-dodecanone caused a clear dose- and time-dependent toxicity in most of the selected biomarkers; significant effects were detected even after 24-h acute exposures. Longer treatments (96h) triggered a general repression of transcription in most of the analysed genes. This study provides novel and interesting results on the toxic effects of an isolated secondary metabolite, naturally present in plants, in C. riparius and highlights the potential suitability of this organism for deep into the molecular effects of plant defences in insects. A deep knowledge of the mode of action of secondary metabolites on development and metabolism of insects, will generate new leads to tap their potential in plant resistance to pests. These findings provide new insights into insecticidal efficacy of 2-dodecanone, which might be explored under field conditions for plant protection and pest management, to reduce reliance on synthetic pesticides. Acknowledgement: This research was supported by the Spanish Ministry of Economy and Competitiveness (AGL2015-67733-R).